Numbers don't lie : new adventures in counting and what counts in basketball analytics - Colás, Santiago, 1965- (University of Nebraska Press, 2020)
"Numbers Don't Lie gives readers a multilayered understanding of basketball analytics on its own terms, describes the historical and contemporary conditions in basketball culture, science, and society that have facilitated the rise of basketball analytics, and shows how the impact of basketball analytics varies from the standpoint of various perspectives that its practitioners and advocates tend to ignore or to discount"--